SOVEREIGN DEBT ISSUANCE CHOICE: SUKUK VS CONVENTIONAL BONDS - Rhada Boujlil; M. Kabir Hassan; Rihab Grassa (Journal of Islamic Monetary Economics and Finance, 2020)
This paper investigates the determinants and their factors that affect governments’ decision to employ sovereign Sukuk over conventional bonds; the research is based on a sample of 143 Sukuk and 602 conventional sovereign bonds issued in 16 OIC countries from 2000 to 2015. The results depict that more nations that have developed financial markets, higher credit quality, and strong economic/financial prospects, issue sovereign Sukuk rather than sovereign conventional bonds. Dealing with Sukuk bonds can be a strategy to diversify and develop current debt markets by introducing newly-developed debt tools. However, less economically developed nations countries are typically issuing insurance for classic sovereign bonds. Our findings suggest that a government’s choice of sovereign debt is influenced mainly from national financial and macroeconomic indicators, as well as specific events. Countries with developed financial markets, strong economic indicators, high credit quality, and sustainable financial position are more likely to issue sovereign Sukuk rather than sovereign bonds as a strategy to develop and diversify their financial markets by promoting new debt products.